Functionality of innovative and generic celluloses in metronidazole formulations (Brazilian Journal of Pharmaceutical Sciences, 2011)
The wide variety of excipients available calls for evaluation of their functionality, in this case of the pharmaceutical performance of microcrystalline celluloses and sodium cross-linked carboxymethylcelluloses from different sources. This evaluation includes parameters such as powder flow, compactibility, ejection pressure and dissolution from fast-release tablets as well as from floating granules and controlled-release tablets. In a previous study, the excipient Carmacel® presented better disintegration properties compared to Croscarmellose®. However, the evaluation showed better compactibility performance for Croscarmellose®. These characteristics were observed using pure excipients. Nevertheless, these advantages have not been confirmed in tests employing immediate-release or modified-release formulations containing metronidazole. Regarding microcrystalline celluloses, the present comparative evaluation between pure Alfacel ® types 101 and 102 and pure Avicel® types 101 and 102 showed better compactibility performance for the latter. However, for metronidazole formulations, this advantage was not evident in the innovative excipient. Notwithstanding, this study revealed better compactibility performance of microcrystalline cellulose type 101. In terms of powder flow properties, Avicel® and Alfacel® showed similar performance. However, the results revealed better powder flow employing microcrystalline cellulose type 102 for both excipients. Based on the results obtained, it can be concluded that the employment of innovative and generic excipients have both advantages and disadvantages. The observed differences however, tend to disappear as the excipients are diluted in a formulation, thereby equalizing their influence on product performance.